Prototype Catfish Seed Calculator Using Arduino Uno in Cloudy Water - Fauzi Sahlan Rizki Sinaga; Muhammad Daud; Misbahul Jannah; Rosdiana Rosdiana (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2023)
Since Indonesia is an archipelagic nation, the economic sector of fisheries, particularly catfish farming, is one that has a lot of potential. However, a lot of catfish breeders still count their fish seeds by hand, which is time-consuming, particularly in hazy water conditions. Therefore, an automatic catfish seed counter is required in order to make calculations simpler, quicker, and more precise even under hazy water situations. In order to address these objectives, the prototype of a catfish seed counting device in murky water is shown in this study. This tool's prototype was created and constructed utilizing an Arduino Uno as the processor, two different types of sensors as inputs, and an LCD and buzzer as outputs. The FC-51 proximity sensor is used to count the quantity of fish seeds, while the turbidity module sensor measures the amount of turbidity in the water. With a total sample size of 50 fish fry, the test was run under three conditions for the turbidity level of the water samples: 6.21 NTU, 11.10 NTUs, and 16.38 NTU. According to the test results, the catfish seed counter in murky water performed admirably and was fairly accurate. An average error value of 3.2% is achieved with a water turbidity value of 6.21 NTU. An average error value of 6.8% was discovered at the turbidity value of 11.10 NTU. Finally, an average error value of 18.8% was discovered at a water turbidity value of 16.38 NTU. In order for this catfish seed counter to be effective, water turbidity values below 13 NTU with a minor error of 10% are preferred, particularly water turbidity values below 8 NTU with a little error of 5%.